1988
DOI: 10.1037/h0091754
|View full text |Cite
|
Sign up to set email alerts
|

The Visual Reproduction subtest: Standardization and clinical validation of a delayed recall procedure.

Abstract: This study provided a normative data base for a Delayed Recall procedure using the Visual Reproduction subtestfrom Form I of the Wechsler Memory Scale and examined the test's clinical sensitivity in four groups of patients . Normative data were based on 255 neurologically normal adults (age range 18-91). Clinical groups included patients with severe head trauma (n = 34), left hemisphere CVA (n = 13), right hemisphere CVA (n = 43), and Alzheimer's Disease (n = 13). Analysis of normative data revealed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 20 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Subjects were administered the VSRT along with a battery of neuropsychological tests as part of a broader standardization study. These tests included the Expanded Paired Associate Test (Trahan et al, 1989), Continuous Visual Memory Test (Trahan & Larrabee, 1988; Trahan et al, 1990), and the Wechsler Memory Scale Visual Reproduction Subtest with Delayed Recall (Russell, 1988; Trahan et al, 1988). All subjects were tested by one of us or a well-trained assistant, in a comfortable and private office.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects were administered the VSRT along with a battery of neuropsychological tests as part of a broader standardization study. These tests included the Expanded Paired Associate Test (Trahan et al, 1989), Continuous Visual Memory Test (Trahan & Larrabee, 1988; Trahan et al, 1990), and the Wechsler Memory Scale Visual Reproduction Subtest with Delayed Recall (Russell, 1988; Trahan et al, 1988). All subjects were tested by one of us or a well-trained assistant, in a comfortable and private office.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between normal aging and memory performance has been the subject of numerous scientific investigations. Collectively, these studies have demonstrated that older adults perform below levels obtained by younger ones on a variety of acquisition-learning tasks (Rankin & Kausler, 1979; Riege & Inman, 1981; Trahan, Larrabee, & Quintana, 1990; Trahan, Larrabee, Quintana, Goethe, & Willingham, 1989; Trahan, Quintana, Goethe, & Willingham, 1988). Age differences occurred regardless of the type of stimulus used (i.e., verbal or visual), retrieval format (i.e., recall or recognition), or modality of presentation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A number of studies also have examined age differences in long-term retrieval, using delayed-recall or recognition procedures (Larrabee et al, 1988;Russell, 1988;Rybarczyk, Hart, & Harkins, 1987;Trahan et al, 1988Trahan et al, , 1989Trahan et al, , 1990. These investigations have demonstrated that older adults also perform below levels obtained by younger ones on a variety of measures employing delayed-retrieval tasks.…”
mentioning
confidence: 99%
“…1. Wechsler Memory Scales-Visual Reproduction subtest: While some authors have found a slight superiority of men on this task (Ivison, 1977), others have found no gender differences (Saykin et al, 1995;Trahan, Quintana, Willingham, & Goethe, 1988).…”
Section: Nonverballvisual Memorymentioning
confidence: 88%